Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): antimicrobial‐resistant Escherichia coli in dogs and cats, horses, swine, poultry, cattle, sheep and goats - EFSA Panel on Animal Health and Welfare (AHAW); Søren Saxmose Nielsen; Dominique Joseph Bicout; Paolo Calistri; Elisabetta Canali; Julian Ashley Drewe; Bruno Garin‐Bastuji; José Luis Gonzales Rojas; Christian Gortázar; Mette Herskin; Virginie Michel; Miguel Ángel Miranda Chueca; et al. (EFSA Journal, 2022)
Abstract Escherichia coli (E. coli) was identified among the most relevant antimicrobial‐resistant (AMR) bacteria in the EU for dogs and cats, horses, swine, poultry, cattle, sheep and goats in previous scientific opinions. Thus, it has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on its eligibility to be listed, Annex IV for its categorisation according to disease prevention and control rules as in Article 9 and Article 8 for listing animal species related to the bacterium. The assessment has been performed following a methodology previously published. The outcome is the median of the probability ranges provided by the experts, which indicates whether each criterion is fulfilled (lower bound ≥ 66%) or not (upper bound ≤ 33%), or whether there is uncertainty about fulfilment. Reasoning points are reported for criteria with uncertain outcome. According to the assessment here performed, it is uncertain whether AMR E. coli can be considered eligible to be listed for Union intervention according to Article 5 of the AHL (33–66% probability). According to the criteria in Annex IV, for the purpose of categorisation related to the level of prevention and control as in Article 9 of the AHL, the AHAW Panel concluded that the bacterium does not meet the criteria in Sections 1, 2, 3 and 4 (Categories A, B, C and D; 0–5%, 5–10%, 10–33% and 10–33% probability of meeting the criteria, respectively) and the AHAW Panel was uncertain whether it meets the criteria in Section 5 (Category E, 33–66% probability of meeting the criteria). The animal species to be listed for AMR E. coli according to Article 8 criteria include mammals, birds, reptiles and fish.